Role of diagnostic laparoscopy in chronic and recurrent pain abdomen - Jagarlamudi, Tejaswi; Ul Hassan, Mir Mohammed Noor (International Surgery Journal, 2020)
Background: Chronic and recurrent abdominal pain of unknown origin represents a significant problem in surgical patients and poses a diagnostic dilemma. With advances in optics, laparoscopy allows visualisation of entire peritoneal cavity and further makes histological diagnosis possible. The rapidly increasing popularity of laparoscopy may be attributed to several factors including its applicability in both emergency and elective settings, high diagnostic yield, therapeutic management in the same setting, low patient morbidity, reduced hospital stays and expenditure. The objective of the study was to evaluate the role of diagnostic laparoscopy in chronic and recurrent pain abdomen. Methods: We conducted a prospective descriptive study on 50 patients who suffered from chronic and recurrent pain in abdomen for more than 3 months with inconclusive clinical or radiological diagnosis. All patients were subjected to diagnostic laparoscopy and findings were noted down. Therapeutic procedures were conducted at the same setting wherever indicated. Histopathological evaluation reports were followed up. Results: Out of 50 patients, laparoscopy established diagnosis in 44 patients, proving diagnostic efficacy at 88%. The most common finding at diagnostic laparoscopy was appendicitis (28%), followed by adhesions (24%). Other findings were tuberculosis (16%), pelvic inflammatory disease (8%), endometriosis (3%), partial torsion of ovarian cyst (4%), cholecystitis (2%). However, diagnostic laparoscopy showed normal study in 6 patients (12%). Appendicectomy followed by adhesiolysis were the most common procedures performed. Conclusions: Recurrent appendicitis is the most common cause of chronic and recurrent pain abdomen. Diagnostic laparoscopy is a safe and effective modality for both diagnostic and therapeutic management of such patients.